UWAGI O JĘZYKU PROPAGANDY POLITYCZNEJ W PRASIE POLSKOJĘZYCZNEJ WYDAWANEJ W ZSRR W OKRESIE MIĘDZYWOJENNYM (NA PRZYKŁADZIE „TRYBUNY RADZIECKIEJ”) - Graczykowska, Tamara (Acta Neophilologica, 2014)
This paper discusses the linguistic characteristics of political propaganda texts written in Polish, extracted from “Trybuna Radziecka,” a central Polish weekly published in Moscow in 1927–1938 and edited by Polish left-wing intelligentsia, living in this period in the USRR as political émigrés. The propaganda creates the world which is different from the real one and this world is always tendentious, up to point of being fictitious. The author attempts to demonstrate that many linguistic characteristics are common to all periods of Polish propaganda. The Polish press published in Moscow in the interwar period initiated the creation of the political socialist Polish post-war propaganda. There are seven fundamental properties which constitute the persuasive dimension of propaganda texts: importance, universality, proximity, necessity, legitimacy, coherence, progress, and permanence. The persuasive function of propaganda texts is achieved by such words as słuszny [legitimate], podstawowy [fundamental], zasadniczy [principal], kluczowy [key], masy [the masses], każdy [everyone], wszyscy [all], powszechny [universal] etc.